Modeling of diesel particulate filter (DPF) - Obadah, Almasri (My University, 2022)
Diesel engines using are still expected, especially for inland and sea transport. Recently, legislation in the European Union has been tightened to reduce emissions from diesel engines and increase fuel efficiency. To meet these needs, an exhaust system must be developed. The diesel particulate filter (DPF) is the part responsible in the exhaust system for purifying most of the soot particles harmful to humans and the environment. This project aims to study the effect of pressure drop on soot loading, where the pressure drop rises with the steadily increasing amount of soot. Therefore, the attempt to influence the pressure drop helps improve the efficiency of soot filtration inside the DPF. The software used was Axisuite, a commercial program developed by Exothermia to study the exhaust system of diesel engines, where the model was created entirely identical in terms of dimensions and the type of materials with what was used in the experiment. The engine Volvo HD D13 was used during the experiment to collect data. The experiment data was collected during custom-made test cycle to understand soot formation and its effect on pressure drop under different engine working conditions. The main parameters that have been checked for influence on the pressure drop are wall permeability, diffusion mechanism correction factor, interception mechanism correction factor, and soot reaction speed inside the diesel particle filter to better agree with the experimental data. The results from the model show that the pressure drop is significantly improved with the experimental data and thus its effect on soot loading. The model also allows comparing sure reduction when using the same porosity-permeability wall and a different permeability.
Keywords: Diesel particulate filter, Axisuite, Parameter estimation, Diesel oxidation catalyst.